Analisis Kekuatan Rangka Mesin Perontok Padi Menggunakan Solidworks 2019 - Ismail Furqani; Rudi Kurniawan Arief; Muchlisinalahuddin Muchlisinalahuddin (Jurnal Engine: Energi, Manufaktur, dan Material, 2022)
Indonesia is one of the largest rice producers in the world. technological developments created a rice threshing machine to facilitate the work of farmers. In the manufacture of the engine frame, of course, must be calculated accurately. Here the SolidWorks 2019 application is used to make it easier to analyze the strength of the rice threshing machine frame. In the simulation of the strength of the frame using SolidWorks 2019, the type of material used is ASTM A36 Steel, and loading is carried out on the frame with a load of 1 of 50 kg and a load of 2 of 30 kg. The simulation results get the largest von misses stress value at load 2 of 79,183,792,000 N /m2 with a displacement of 0.657 mm. The safety factor values obtained from the simulation results are 3 and 2,635. Based on Dobrovolsky in the book "machine element" the safety factor range for dynamic loads is 2.0 - 3.0, then the strength of the frame of the rice thresher machine is able to support the performance of the machine during use.